Supplementation of broiler diets with high levels of microbial protease and phytase enables partial replacement of commercial soybean meal with raw, full‐fat soybean. Issue 3 (22nd February 2018) - Erdaw, M. M.; Perez‐Maldonado, R. A.; Iji, P. A.
Summary: A 3 × 3 + 1 factorial, involving three levels of protease (0, 15, 000 or 30, 000 PROT/kg) and three levels of phytase (1, 000, 2, 000 or 3, 000 FYT/kg), was used to evaluate the effect of replacing commercial soybean meal (SBM) with raw, full‐fat soybean (RFSB) at 75 g/kg of diet for broilers. A control diet was used for comparison. Each treatment was replicated six times, with nine birds per replicate. The concentration of trypsin inhibitors (TIs) in the test diets was approximately 10, 193.4 TIU/kg. Regardless of enzyme supplementation, feed intake (FI) and body weight gain (BWG) of birds in the control group were superior to those on the test diets. Birds that received the protease‐free test diets had reduced FI and BWG, but when supplemented with protease, were similar to the control diet in BWG, FI (except 0–35 days) and feed conversion ratio (FCR). When the test diet was supplemented with elevated levels (extradose) of protease and phytase, the BWG was improved during 0–10 days ( p = .05) and 0–24 days ( p < .01). Regardless of protease supplementation, the weight of thighs was lower for birds fed the test diets. Birds that received the control diet had smaller weight of pancreas. Increasing the level of phytase supplementation reduced ( p < .05) the weight of the pancreas. The apparent ileal digestibility (AID) of CP and AA was higher in birds on the control diets, but this was also improved in test diets by protease supplementation. The activities of trypsin (7%), general proteolytic (11%) and lipase (12%) were slightly increased because of protease supplementation. Mucosal depth and apparent villus surface areas were increased by about 2.9% and 20%, respectively, due to supplementation of elevated level of phytase. It can be concluded that RFSB could partially replace SBM in broiler diets, provided the diets are supplemented with elevated levels of protease and phytase.